Λr -sets and separation axioms - Jeyanthi, M. J.; Kilicman, Adem; Missier, S. Pious; Thangavelu, Periannan (Universiti Putra Malaysia Press, 2011)
Separation axioms are among the most common and important and interesting concepts in topology as well as in bitopologies. In this paper, we introduce Λr-sets and some weak separation axioms using Λr -open sets and Λr -closure operator.